Surveillance of Zoonotic Pathogens and Taxonomic Identification of Non-volant Small Mammals in Peninsular Malaysia - Zhen Yun Siew; Nazifah Fitriyah Zariman; Wan Siti Mariam Wan Sa’idi; Zi Yi Lui; Harriydra Sai Muthu Coomarhesan; Isaac Seow; Nur Juliani Shafie; Siew Tung Wong; Mohd Firdaus Ariff Abdul Razak,; Millawati Gani; Syriswin Wesdy Sindang; Kenny Voon (Tropical Life Sciences Research, 2026)
Malaysia’s tropical rainforests host a rich biodiversity, including various nonvolant small mammals. Among these, murid rodents (family Muridae) are ecologically significant and frequently associated with zoonotic pathogens, making them important subjects for public health research. In recent years, treeshrews (family Tupaiidae), small omnivorous mammals once grouped with primates, have also gained increasing scientific attention due to their unique evolutionary position and emerging role in disease ecology. Rapid species identification is vital for effective surveillance, particularly in the context of emerging infectious diseases. In this study, PCR amplification targeting mitochondrial and nuclear DNA regions was performed using a range of primers, followed by Sanger sequencing to validate the amplicons. Among the primers tested, mcb398 and mcb869, targeting the mitochondrial cytochrome b gene, proved most effective, yielding consistent amplification and high-quality sequences for both rodents and treeshrews. Besides, 22 animals were captured and screened for selected zoonotic pathogens. Paramyxoviruses, coronaviruses, picornaviruses, orthoreoviruses and Dengue viruses were not detected in the faecal samples of rats, Asian house shrews and palm civets. However, mammalian orthoreovirus type 3 and Dengue virus serotype 2 were detected in one and three faecal samples from treeshrews, respectively. Notably, Tupaia sp. m ZYS-2025, detected in this study, may represent a novel species that has not known to science previously.